Características dos frutos e estudos nutricionais em órgãos vegetativos e produtivos de genótipos de Coffea canephora - Rodrigues, Maria Juliete Lucindo (2023)
The present study consists of two chapters that address the genetic diversity and nutritional characteristics in the productive organs, branches and leaves in Coffea canephora in the north of the state of Espírito Santo, Brazil. The first chapter to study the characteristics of the fruits (weight, percentage of straw/grain), the concentration and accumulation of nutrients in fruits, grains and straw was determined, as well as verify the existence of genetic diversity in 20 genotypes of C.canephora. Fruit collection was carried out manually on the 20 plants between May and June 2021, at the complete maturation of the genotypes. To determine the accumulation and concentration of nutrients, a 2,0 kg sample of fresh coffee was collected and sent to the laboratory, where it was placed in trays and dried in an oven with forced air ventilation at 50°C until mass constant temperature, followed by manual processing, separating the grains and straw and submitting them to chemical analyses. For the grain and straw ratio, a total of 120 fruits of each genotype were collected for processing, submitted to analysis of variance, Scott-Knott test for grouping the means. Genetic diversity was analyzed using the UPGMA hierarchical method, Tocher's method and the relative importance of nutrient accumulations, percentage of grain/straw for predicting genetic diversity. Genetic variability was observed between genotypes for the evaluated traits. The genotypes were divided into six groups, with genotypes 8, 2 and 13 remaining isolated. Genotypes 7, 8, 16 and 17 showed yields of 60% of grains compared to straw. Genotypes 8 and 1 stood out for obtaining greater weight of fruits and grains. Nutrients N-K-Ca and FeMn-B are accumulated in greater quantities in the fruits, making it necessary to adapt mineral fertilizer dosages and splitting. In the second chapter, the objective was to evaluate the distribution of nutrient concentrations in the productive organs, leaves and branches in five conilon coffee genotypes. The collection of pre-identified plagiotropic branches for each genotype was carried out in three phenological phases (flowering, graining and maturation). The branches were sent to the laboratory where the parts were separated (flowers, fruits, leaves and branches), later the fresh mass was determined, then the samples were sent to the forced air oven at 65 °C, until mass constant, to determine the dry mass and to chemical analysis. The concentrations and dry mass of reproductive organs, branches and leaves were submitted to analysis of variance by the F test (p<0.01 and p≤0.05). Statistical analyzes were processed using the SAS (Statistical Analysis System) computer program. For all organs studied, nutrient concentrations were high during the flowering period, and tended to decrease in the last evaluations. The highest concentrations were observed for the productive organs, considering the temporary drains of nutrients, varying according to the genotypes. N and K were the macronutrients found in higher concentrations for the three phenological stages and organs studied, with Fe being the most accumulated micronutrient under the same conditions. The genotypes presented an accumulation above 50% of dry mass for the leaves at flowering, and in the maturation phase, more than 70% of the plagiotropic branches were composed of fruits. The Verdim TA genotype showed lower dry mass values for the branches in the first two phenological stages.